2011
DOI: 10.1603/an10200
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Trap Type, Size, Color, and Trapping Location on Capture of Rhabdoscelus obscurus (Coleoptera: Curculionidae)

Abstract: The New Guinea sugarcane weevil, Rhabdoscelus obscurus) (Boisduval) (Coleoptera: Curculionidae), is a pest of palm plantations, ornamental nurseries, and sugarcane (Saccharum L.). Field and laboratory studies have explored the effects of trap characteristics such as design, size, color, visual and olfactory cues, and location on capture of R. obscurus in date palm plantations and ornamental nurseries at five locations (Dededo, Mangilao, Malojloj, Inarajan, and Yigo) on Guam, USA. Ramp and ground traps captured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
19
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 22 publications
1
19
0
Order By: Relevance
“…Here we provide evidence on whether semiochemical-based lures, developed recently by Reddy et al (2011), can reduce the damage caused by R. obscurus.…”
mentioning
confidence: 88%
See 4 more Smart Citations
“…Here we provide evidence on whether semiochemical-based lures, developed recently by Reddy et al (2011), can reduce the damage caused by R. obscurus.…”
mentioning
confidence: 88%
“…The addition of ethyl acetate to the pheromone lures as a synergist signiÞcantly increased trap catches of R. obscurus, but did not help in controlling R. obscurus (Reddy et al 2005). Additional studies conducted by Reddy et al (2011) to improve the capture efÞciency showed that 40 by 25-cm russet brown ground traps baited with pheromone lures and strapped to the trees are an efÞcient tool for catching R. obscurus in the Þeld. Contrariwise, the authors further reported that indoors, black, but otherwise identical, traps were the most effective.…”
mentioning
confidence: 97%
See 3 more Smart Citations